Exploring STEM Attitudes in Indonesian Elementary Students: A Comparative Analysis of Gender and Grade Level - Wulandari, Fitria; Mirnawati, Lilik Binti (FKIP Universitas Lampung, 2025)
Amidst the rapid development of science and technology, STEM learning has become an essential approach to preparing the younger generation with 21st-century skills. However, in Indonesia, interest and positive attitudes toward STEM subjects at the elementary level remain limited. Objective: This study aims to examine students’ attitudes toward STEM and identify possible differences by gender and grade level among fourth and fifth-grade students in an elementary school in Sidoarjo, Indonesia. Methods: A quantitative cross-sectional comparative design was employed, involving 314 students with 167 males (53.18%) and 147 females (46.81%). Data were collected using the STEM Attitude Scale for upper elementary students, developed by Unfried, with internal reliability coefficients ranging from α = 0.83 to α = 0.87. The data were analysed using normality and homogeneity tests, independent-samples t-tests, and effect size calculations (Cohen’s d). Focus group interviews were also conducted to complement the quantitative data. Findings: The results showed students’ attitudes toward STEM are positive. Moreover, it was found that there are no significant differences in overall STEM attitudes by gender or grade level. Although no statistically significant difference was observed, a small-to-medium effect (d = 0.30) in the science aspect suggested that younger students tended to express slightly higher enthusiasm for science-related learning. Furthermore, findings from the interviews indicate that students’ attitudes toward STEM influence their perceptions of their desired future careers or professions. Overall, the findings of this study are largely consistent with those of previous studies. Conclusion: The findings suggest that gender and grade-level differences in STEM attitudes among elementary students are minimal, indicating that early, inclusive, and hands-on STEM education may effectively promote equal engagement and interest across these groups. This study is limited by the small sample size, limited variables, and quantitative approach; therefore, future research should involve more schools and explore how STEM attitudes relate to students’ interest in STEM careers. Keywords: STEM education, attitude, gender, grade level.